Neuropathology does not Correlate with Regional Differences in the Extent of Expansion of CTG Repeats in the Brain with Myotonic Dystrophy Type 1 - Funakawa, Itaru; Kawamoto, Kunihiko; Jinnai, Kenji; Itoh, Kyoko; Mitani, Maki; Fushiki, Shinji; Futamura, Naonobu (ACTA HISTOCHEMICA ET CYTOCHEMICA, 2010)
Myotonic dystrophy (DM1) is known to be an adult-onset muscular dystrophy caused by the expansion of CTG repeats within the 3' untranslated region of the dystrophin myotonin protein kinase (DMPK) gene. The clinical features of DM1 include CNS symptoms, such as cognitive impairment and personality changes, the pathogenesis of which remains to be elucidated. We hypothesized that the distribution of neuropathological changes might be correlated with the extent of the length of the CTG repeats in the DMPK genes in DM1 patients. We studied the neuropathological changes in the brains of subjects with DM1 and investigated the extent of somatic instability in terms of CTG repeat expansion in the different brain regions of the same individuals by Southern blot analysis. The neuropathological changes included état criblé in the cerebral deep white matter and neurofibrillary tangles immunoreactive for phosphorylated tau in the hippocampus and entorhinal cortex, both of which were compatible with the subcortical dementia in DM1 patients. However, the length of the CTG repeats did not correlate with the regional differences in the extent of neuropathological changes. Our data suggested that pathomechanisms of dementia in DM1 might be more multifactorial rather than a toxic gain-of-function due to mutant RNA.